A Study to Evaluate the Effectiveness of a Structured Teaching Programme (STP) on Knowledge Regarding the WIFS Programme among Adolescents of Selected Schools at Chamarajanagar - MB, Mahadevaprasad; G, Vinay Kumar; Khan, Inayath Ulla (International Journal of Research in Medical Surgical Nursing, 2024)
Background & Objectives Adolescence is a vulnerable period in the human life cycle for the development of nutritional anemia, which has been constantly neglected by public health programs and is at high risk of iron deficiency anemia due to accelerated increase in requirements for iron, as well as the social norm of early marriage and adolescent pregnancy. Therefore, adolescents, especially girls between 12–15 years, are vulnerable to iron deficiency anemia because this phase requires high requirements. Statement of the Problem "A Study to Evaluate the Effectiveness of Structured Teaching Programme (STP) on Knowledge Regarding WIFS Programme among Adolescents of Selected Schools at Chamarajanagar." Methodology The research approach adopted for the study was evaluative, using a quasi-experimental study design. In this study, the independent variable is the structured teaching program on the WIFS program, and the dependent variable is the knowledge of adolescents regarding the WIFS program. Background factors were demographic variables such as age, gender, educational status, mother and father's education, family income per month, type of diet, area of living, knowledge of the WIFS Programme, and previous history of anemia. Results The results show that in the pre-test, most adolescent school children (68.3%) had poor knowledge of the WIFS program. Still, in the post-test, the majority of the teenage school children (73.3%) had an average understanding of the WIFS program, mean percentage of the post-test level of knowledge score that is M=14.75 (54.62%), SD =4.25 were higher than the mean of pre-test level of knowledge score that is M=7.57(28.03%), SD =4.19. The paired 't' test computed between pre and post-test knowledge scores was statistically significant at 0.05 level of significance. The calculated ‘t’ value of 11.17 is greater than the table value(t(59))=1.96. The result shows that there is no association between the gain in knowledge scores with selected demographic variables like educational status (ᵡ2(2)= 4.305), education of mother(ᵡ2(1)=0.15), Family monthly income(ᵡ2(1)=0.0017), type of diet(ᵡ2(1)=1.26), area of living (ᵡ2(1)=0.0063), Knowledge on WIFS (f=0.48), suffered from anemia (f=0.46). However, it is found that there is a significant association between the gain in knowledge scores of adolescent WIFS program among adolescents with selected demographic variables like age (ᵡ2(2)= 8.28 ), sex (ᵡ2(1)= 8.13), education of father (ᵡ2(1)= 4.34). Hence, the research hypothesis was accepted in selected demographic variables like age, sex, and education of the father, and the research hypothesis was rejected in selected demographic variables like educational status, education of the mother, family monthly income, type of diet, area of living, and Knowledge of WIFS, suffered from anemia. Hence, the research hypothesis (H1) is accepted. This shows that the structured teaching program improved adolescent school children's knowledge of the WIFS program. Interpretation and Conclusion The results showed that the mean post-test score was higher than the mean pre-test. There was a significant improvement in knowledge scores among the adolescents after the intervention. Thus, there has been a substantial improvement in adolescents' knowledge of the WIFS program after the administration of a structured teaching program. The study also showed that adolescents must be aware of the WIFS program and its practice to prevent adolescent anemia.